(untitled) (Third Sector Social Economic Review, 2023)
Information technology (IT) has been seen as a critical component supporting economic growth in recent years. IT products and services have become an integral part of economic and social life for individuals and businesses. Information technologies coming to the fore more with globalization and digitalization have positive consequences as well as negative ones such as the increase in the tendency and violence of cybercrime. Cyber-attacks against enterprises, especially small- and medium-sized enterprises (SMEs), have become more frequent and sophisticated in recent years. Considering the increasing frequency and severity of cyber-attacks, the cyber insurance market is expected to continue to grow. In this context, the purpose of this study is to investigate the market practices of cyber insurance in Türkiye and to examine the cyber insurance market. In the study, qualitative research method was employed and semi-structured interview forms were used as data collection tool. As a result of the interviews with representatives from the non-life insurance companies participating in the research, the current situation of the cyber insurance market in Türkiye were examined under the headings of underwriting process and pricing, sector preference, requirements on the insured, insurance coverage, and response process when a cyber-incident is suspected. In addition, the effects of Covid-19 outbreak on the cyber insurance market and opportunities and/or obstacles to the cyber insurance market in Türkiye were tried to be revealed.